Предмет: Математика,
автор: Ladybatman468
lg(2x^2+3x)-lg(6x+2)=0
Ответы
Автор ответа:
0
lg(2x²+3x)-lg(6x+2)=0
ОДЗ:
2х²+3х>0 6x+2>0
2x(x+1.5)>0 x>-3
x∈(-3;-1.5)∨(1.5; +∞)
2x²+3x=6x+2
2x²+3x-6x-2=0
2x²-3x-2=0
D=9+4*2*2=25
x₁=(3+5)/4=2
x₂=(3-5)/4=-0.5
ОДЗ:
2х²+3х>0 6x+2>0
2x(x+1.5)>0 x>-3
x∈(-3;-1.5)∨(1.5; +∞)
2x²+3x=6x+2
2x²+3x-6x-2=0
2x²-3x-2=0
D=9+4*2*2=25
x₁=(3+5)/4=2
x₂=(3-5)/4=-0.5
Похожие вопросы
Предмет: Другие предметы,
автор: alrud1958
Предмет: Математика,
автор: catc28
Предмет: Математика,
автор: nurmametovazamira724
Предмет: Информатика,
автор: popigun911